Optimising canopy size and structure in field beans (Vicia faba) grown in a temperate climate - Murphy, Leona (2021)
Field beans are an up-and-coming crop in Irish agriculture, helping to reduce imports of feed protein and encouraging a home-grown source for cattle feed. Since the introduction of the protein grant in 2015 as part of the Common Agricultural Policy (CAP) greening scheme, the area of field beans sown in Ireland has increased rapidly. However, due to their unpredictable year on year variation in yield, field beans have not yet reached their full potential in Irish agriculture. A better understanding of their growth and development as well as management of the crop for full yield potential is essential to encourage growers to avail of the added benefits of having field beans in their crop rotations.